COMPARISON OF ENDOSCOPIC PILONIDAL SINUS TREATMENT (EPSIT)WITH KARYDAKI’S PROCEDURE IN THE MANAGEMENT OF PILONIDAL SINUS (The Research of Medical Science Review, 2025)
Background: Pilonidal sinus disease (PD) commonly affects young adults and often requires surgery. The Karydakis procedure and Endoscopic Pilonidal Sinus Treatment (EPSiT) are two common techniques. Differences in hospital stay and recurrence rates between them remain clinically important. Comparing these can aid in selecting the optimal treatment. Objective: To compare the outcomes of Karydakis procedure and Endoscopic Pilonidal Sinus Treatment (EPSiT) in terms of hospital stay and recurrence rate in patients with pilonidal sinus disease (PD). Methods: This randomized controlled trial was conducted in the Department of Surgery at Services Hospital, Lahore, over a period of six months (September 1, 2024 to March 1, 2025). Using non-probability successive sampling and randomly allocated into Group A (Karydakis procedure) and Group B (EPSiT), a total of 92 patients with clinically and radiologically verified pilonidal sinus were enrolled: 46 individuals each. There was only one surgical team handling all of the operations. We noted postoperative results including hospital stays and recurrences. While recurrence was clinically and radiologically evaluated at three months, hospital stay was computed from the day of operation till release. SPSS v21 was used for data analysis; chi-square test was used for recurrence; Mann-Whitney U test for hospital stay. A p-value ≤ 0.05 was considered statistically significant. Results: Between both groups, baseline parameters like age, gender, and illness duration were comparable (p > 0.05). The mean hospital stay in the EPSiT group (3.19 ± 1.51 days) was much less than in the Karydakis group (6.72 ± 2.14 days) (p < 0.001). With a p = 0.002, the recurrence rate was much greater in the Karydakis group (28.3%) than in the EPSiT group (4.3%). Stratified analysis revealed notably greater recurrence with Karydakis in men (35.5% vs. 3.4%, p = 0.002), patients aged 16–30 years (34.4% vs. 3.1%, p = 0.002), and in those with illness duration ≥6 months (26.5% vs. 2.7%, p = 0.004). Conclusion: With much reduced hospital stay and decreased recurrence rates, EPSiT proved better than the Karydakis technique. These results help to justify the use of EPSiT as a less invasive, successful substitute for pilonidal sinus disease surgical treatment.